2013
DOI: 10.1080/1068316x.2013.793766
|View full text |Cite
|
Sign up to set email alerts
|

Economically disadvantaged juvenile offenders tried in adult court are perceived as less able to understand their actions, but more guilty

Abstract: We investigated the influence of a juvenile defendant's socioeconomic status (SES) on mock jurors' perceptions of a juvenile tried in adult court. As predicted, participants convicted the low SES juvenile defendant of felony murder significantly more than the middle or high SES juvenile defendant. Yet, participants also rated the low SES juvenile as less mature than the middle or high SES juvenile Á a belief that past research shows predicts leniency in verdicts (i.e., not guilty judgments). Finally, stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Moreover, a meta-analysis of studies on mock juror judgments showed that low SES defendants were found guilty more easily and received greater punishment for their crimes than did others, indicating jurors’ bias against low SES defendants ( Mazzella and Feingold, 1994 ). This finding was also verified in a recent study ( Farnum and Stevenson, 2013 ). In addition to explicit prejudice against low-SES people, participants also express implicit pro-rich attitudes ( Horwitz and Dovidio, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, a meta-analysis of studies on mock juror judgments showed that low SES defendants were found guilty more easily and received greater punishment for their crimes than did others, indicating jurors’ bias against low SES defendants ( Mazzella and Feingold, 1994 ). This finding was also verified in a recent study ( Farnum and Stevenson, 2013 ). In addition to explicit prejudice against low-SES people, participants also express implicit pro-rich attitudes ( Horwitz and Dovidio, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…For instance, in the US, a typical criminal is seen as low-SES, and in mock jury studies low-SES offenders receive longer sentences than higher income offenders. Less is known about juvenile delinquents, who nowadays are more and more tried in adult courts, where they receive more severe punishments compared to juvenile courts [51]. In an experimental study, despite the low- (vs. high-) SES juvenile offender being more often found guilty and to a greater extent, he was also perceived as less capable of understanding the criminal court process and the consequences of his actions (i.e., less intelligent) and less mature.…”
Section: Stereotypes In Cross-class Encountersmentioning
confidence: 99%
“…The harsher verdict toward the low-SES juvenile seemed in fact partially explained by the negative stereotype as a superpredator (i.e., cold and calculating). Therefore, paradoxically, the verdict is harsher, although the low-SES offender is considered less responsible [51]. …”
Section: Stereotypes In Cross-class Encountersmentioning
confidence: 99%
“…The primary goals of the juvenile justice system, in addition to maintaining public safety, is to development skills, rehabilitation, addressing any treatment needs, and successful reintegration of youth into the community (Skowyra & Cocozza, ). Transferring juveniles to adult courts through certification has serious ramifications for marginalized juvenile offenders, especially racial minorities and those in poverty who are often overrepresented in the juvenile justice system (Farnum & Stevenson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Negative stereotypes about the criminality of Black juvenile offenders might drive legal decision‐makers to treat them more punitively than similar White juvenile offenders (Farnum & Stevenson, ) due to their disproportionate exposure to circumstances, both in and out of custody, that not only act as barriers to healthy development, but also contribute to and exacerbate the high rate of emotional problems and recidivism found in this population (Evans‐Chase, ).…”
Section: Introductionmentioning
confidence: 99%